Analysis of hydraulic behavior in pressurized systems with different automation mechanisms using Neutrosophic SuperHyperSoft sets - Santiago Salomon Chicaiza-Toapaxi; Anthony Alexander Ortega-Toapanta; Héctor Luis Laurencio-Alfonso (Neutrosophic Sets and Systems)
Residential pressurization has significantly influenced energy consumption, particularly in systems with low-power pumps. Therefore, this study assessed the hydraulic and energy performance of three configurations: a centrifugal pump with presscontrol, a hydropneumatic system, and a hybrid system, structured using Neutrosophic SuperHyperSoft Sets. The results indicated that the presscontrol system exhibited the highest efficiency (22.48%), followed by the hybrid system (21.62%) and the hydropneumatic system (20.17%), with minimal differences in operational flow rates. It was concluded that although these systems do not meet high-demand scenarios, they are efficient for most common sanitary fixtures, optimizing energy consumption and sustainability in residential and industrial environments. Future studies are recommended to evaluate attributes with varying degrees of neutrosophic membership to validate their technical, economic, and environmental feasibility under different demand conditions.